Evaluation of the dental casts measurements using caliper and 3D laser scanning: Preliminary results - Tahir, Zie Zie Azeanty; Setan, Halim; Majid, Zulkepli; Suwardhi, Deni; Samsuri, Abd. Rani (2006)
Measurements and different analyses of dental casts are essential for precise diagnosis of an orthodontic case. At present, virtual computerized models, such as from Laser Scanning, are available for clinicians, supplemented by dedicated software for performing the required measurement. The purpose of this study is to measure and compare a set of dental casts using calipers and Laser Scanning. Impressions were taken from the patients, providing 9 dental cast and 9 virtual (laser scanning) models. Measurements of arc width and arc perimeter were made on both, while measurements of palatal length and palatal depth were difficult to obtain using calipers but can be done on the computerized models (using RapidForm software). Some preliminary results are shown to illustrate this approach. For the tested clinically applicable methods, measurement with digital calipers on dental cast can give the best accuracy but in certain case this method cannot be used accurately such as palatal depth and palatal length. However, computerized (Laser Scanning) models accuracy is clinically acceptable. In the near future, the 3D virtual model would become the standard tool for orthodontic clinical practice.